Indocyanine-based near-infrared lymphography for real-time detection of lymphatics in a cat with multiple mast cell tumours. Issue 1 (February 2022) - Arz, Raphael; Seehusen, Frauke; Meier, Valeria S; Nolff, Mirja C
Case summary: An 11-year-old female domestic shorthair cat was presented with cutaneous mast cell tumours (MCTs) localised at the right temporal region, the left buccal region and on the third digit of the right thoracic limb. Staging was negative and locoregional lymph nodes appeared normal, based on clinical findings. During surgery, real-time indocyanine green (ICG)-based lymphography was performed to detect the cutaneous draining pattern of all the primary MCTs. ICG was injected intracutaneously in four quadrants around each tumour, and a clear lymphogram was visible shortly after injection. Using near-infrared lymphography (NIR-L) for guidance, all lymphadenectomies were performed in 12 mins or less, with a maximal incision length of 3.5 cm. The smallest resected node was 0.9 cm in diameter. All MCTs were classified as low-grade cutaneous MCT. All four ICG-positive lymph nodes were considered premetastatic or metastatic. The only ICG-negative resected node was also negative for tumour cells. No complications related to NIR-L were recorded. Relevance and novel information: This is the first description of NIR-L in a cat with MCT. Application was straightforward and ICG enrichment only occurred in the metastatic nodes, suggesting correct identification of lymphatic draining patterns. Of note, as previously described in dogs, we did detect nodal metastasis, despite low-grade primary tumours. The clinical relevance should be evaluated in future studies.